Comparison of the Reactivity of the Three Distonic Isomers of the Pyridine Radical Cation Toward Tetrahydrofuran in Solution and in the Gas Phase - Widjaja, Fanny (2013)
The reactivity of the three distonic isomers of the pyridine radical cation toward tetrahydrofuran is compared in solution and in the gas phase. In solution, the distonic ions were generated by UV photolysis at 300 nm from iodo-precursors in acidic 50:50 tetrahydrofuran/water solutions. In the gas phase, the ions were generated by collisionally activated dissociation (CAD) of protonated iodo-precursors in an FT-ICR mass spectrometer, as described in the literature. The same major reaction, hydrogen atom abstraction, was observed in solution and in the gas phase. Attempts to cleave the iodine atom from the 2-iodopyridinium cation in the gas phase and in solution yielded the 2-pyridyl cation in addition to the desired 2-dehydropyridinium cation. In the gas phase, this ion was ejected prior to the examination of the desired ion’s chemical properties. This was not possible in solution. This study suggests that solvation effects are not significant for radical reactions of charged radicals. On the other hand, the even-electron ion studied, the 2-pyridyl cation, shows substantial solvation effects. For example, in solution, the 2-pyridyl cation forms a stable adduct with tetrahydrofuran, whereas in the gas phase, only addition/elimination reactions were observed.